How should we approach negative news in the media? A ‘mindful’ and ‘harmonious’ consumption of negative news by users might be an answer - Shabahang, Reza; Weber, René (Frontiers in Psychology, 2025)
The prevalence of negative sentiment in news content appears to have increased over time. This trend has raised concerns about the potential challenges associated with consuming negative news, particularly when it is consumed frequently. In response, two general recommendations have emerged: news organizations should strive to balance negative coverage with positive reporting, and users are advised to limit their exposure to negative news. However, these recommendations seem to not be effective in practice in many cases and may also raise moral, intellectual, informational, and societal challenges (e.g., the public’s unawareness of societal issues). This Perspective aims to propound that negative news can be consumed ‘mindfully’ and ‘harmoniously’. We propose that individuals should adopt an agentic mindset toward negative news consumption. We outline what mindful and harmonious consumption of negative news might look like and argue that recommending a fixed duration limit for exposure to negative news for all users may not be feasible, given the interpersonal and intrapersonal variability among individuals. The mindful-harmonious consumption of negative news may serve as an adaptive strategy for contemporary users, who are continuously exposed to negative news yet still require it. Conceptual and empirical investigations into the mindful and harmonious consumption of negative news warrant scholarly and public attention.